ANALYSIS OF USE OF REMAINING MORE FINANCIAL BUDGET FINANCING, ANALYSIS OF THE USE OF BACKUP FUNDS AND DIVESTMENT ANALYSIS OF MANAGEMENT OF BUDGET INCOME BUDGET INCOME ON THE GOVERNMENT OF BINJAI CITY - Mariyam, Mariyam (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2019)
The purpose of this study was to determine and analyze whether the use of SiLPA last year, the use of reserve funds, the use of divestment on the management of the local budget in Binjai City Government. The analytical method used in my research is a quantitative method, by testing classic assumptions before getting a good research model. The variables in this study are the use of SiLPA last year, the use of reserve funds and the use of divestment as an independent variable and the level of APBD management as the dependent variable. The population of this study uses the Position of Financial Statements in 2014- 2015. The results of this study prove that partially the use of SiLPA last year, The use of Reserve Funds and the Use of Divestment have a significant effect on the Regional Budget Management in Binjai City. This is explained in the Adjusted R Square of 13.3%. The APBD management variable can be explained by the existing independent variables namely the use of SiLPA last year, Use of Reserve Funds and Use of Divestment have an effect on on APBD Management. The remaining 97.7% is influenced by other variables not explained by this research model, but the increase in acceptance of the use of SiLPA last year, the use of Reserve Funds, the use of Divestment, this is evidenced by the relationship has not been able to significantly improve the management of APBD. 3% of the APBD management variable can be explained by the independent variables, namely the use of SiLPA last year, the use of Reserve Funds and the use of Divestment have an effect on the APBD Management. The remaining 97.7% is influenced by other variables not explained by this research model, but the increase in acceptance of the use of SiLPA last year, the use of Reserve Funds, the use of Divestment, this is evidenced by the relationship has not been able to significantly improve the management of APBD. 3% of the APBD management variable can be explained by the independent variables, namely the use of SiLPA last year, the use of Reserve Funds and the use of Divestment have an effect on the APBD Management. The remaining 97.7% is influenced by other variables not explained by this research model, but the increase in acceptance of the use of SiLPA last year, the use of Reserve Funds, the use of Divestment, this is evidenced by the relationship has not been able to significantly improve the management of APBD